A study of CBS gene polymorphism, plasma H2S levels and their association in type-2 diabetes mellitus - Dasgupta, Sayantan; Mondal, Ishita; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2018)
Background: Hydrogen Sulphide (H2S), in recent years, is getting significant attention, as more evidences are emerging about its diverse biological roles. There are evidences of H2S having anti-inflammatory, neuro-modulator, vasodilator, anti-apoptotic and mitochondrial protective roles in various tissues. Among different tissues, β-cells of pancreas, according to some recent studies, get significantly affected by the imbalance in H2S homeostasis, leading to β-cell dysfunction and Diabetes Mellitus (DM). Cystathionine- β-synthase (CBS) enzyme is involved in the synthesis of H2S from cysteine in various tissues. Among various possible mutations in the CBS gene, a particular 833T-C mutation, has been found to be associated with various diseases.Aims and Objectives: The present study was aimed to determine the extent of abnormality of H2S homeostasis in type-2 DM patients, and to find out presence and association (if any) of 833T-C mutation in CBS gene, in the patients of type-2 DM, in comparison to healthy control subjects, in the Indian population.Materials and Methods: A cross sectional study was done with 40 clinically and biochemically diagnosed DM type II patients attending OPD of Endocrinology department of NRS Medical College & Hospital, Kolkata, and 40 age and gender matched non-diabetic control subjects. DNA was isolated from EDTA blood of all the study subjects, PCR done and results compared. Plasma H2S was measured by the N,N-dimethyl-p-phenylene-diamine method. Plasma glucose and serum insulin were measured by standardized commercial kits.Results: Our study found the plasma H2S levels in the patients of type II DM to be significantly higher(P